Fostering Students’ Descriptive Text Writing Ability: Please Strategy Vs. Idea Details Strategy - Windi Kurniati; M. Sayid Wijaya; Rohmatillah Rohmatillah (State Institute for Islamic Studies IAIN of Metro, 2020)
The aim of this research is to investigate whether is there a significant difference between the use of PLEASE Strategy and Idea Details Strategy in increasing students’ descriptive text writing ability. This research methodology used was a static group comparison. The population of this research was 8th-grade students of the second semester at SMP Negeri 2 Menggala. The total sample in this research was 64 students, chosen by using cluster sampling: VIII A as experimental class A taught by using PLEASE strategy and VIII B as experimental class B taught by using Idea Details strategy. Pre-test and post-test were implemented to collect the data. From the data analysis computed by using SPSS, it was found the result of independent sample t-test Sig. = 0.008 and α = 0.05. It meant that Ha was accepted. There was a significant difference between the use of PLEASE strategy and Ideas Details strategy in increasing students’ descriptive text writing ability.